ANALISIS YURIDIS PERATURAN PEMERINTAH NOMOR 109 TAHUN 2012 TENTANG PENGAMANAN BAHAN YANG MENGANDUNG ZAT ADIKTIF BERUPA PRODUK TEMBAKAU BAGI KESEHATAN - Agung Pribadi Azhari; Mexsasai Indra; Ledy Diana (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
One of the problems that is of concern to the author at this time is thecirculation of cigarettes that is not controlled, anyone can consume cigarettes,including those who are not allowed to consume cigarettes, such as childrenunder the age of 18 and pregnant women. In line with Government RegulationNumber 109 of 2012 concerning the Protection of Materials Containing AddictiveSubstances in the Form of Tobacco Products for Health. In GovernmentRegulation Number 109 of 2012 Concerning the Protection of SubstancesContaining Addictive Substances in the Form of Tobacco Products for Health, itappears that there is an intention to put more emphasis on the distribution ofcigarettes.Therefore, researchers conducted research with a normative approach.Normative legal research is legal research conducted by examining secondarydata or library materials consisting of secondary, tertiary, and primary legalmaterials. In Government Regulation Number 109 of 2012 Concerning theProtection of Materials Containing Addictive Substances in the Form of TobaccoProducts for Health, researchers see a deficiency regarding which agency has theright or responsibility to enforce sanctions that apply in the event of circulation ofcigarettes that are not in accordance with applicable law.In the Juridical Analysis of Government Regulation Number 109 of 2012concerning the Protection of Materials Containing Addictive Substances in theForm of Tobacco Products for Health. Urge the Central Government andRegional Governments to deal with the distribution of cigarettes to categories thatare prohibited from consuming cigarettes by adding or inserting articlesgoverning these agencies in Government Regulation Number 109 of 2012Concerning Control of Substances Containing Addictive Substances in the Formof Tobacco Products for Health or by making Regional Regulations governing thedistribution of cigarettes.Keywords: Juridical Analysis-Addictive Substances-Cigarettes-Agency